THE CONSTRUCTION OF READING HABIT BY AN OVERSEAS STUDENT: THE STORY FROM CZECH TO INDONESIA - Dhinda Azizah Putri; Intan Pradita (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2022)
Current research in Indonesia about reading habits tends to discuss the topic quantitatively instead of exploring the process of how reading habits were developed. Whereas it is necessary to see reading habits as a process of development. Through seeing it as a process, reading habit can be seen as not just a measurable component but more into a sustained lifetime literacy. To fill this void, this research aimed to investigate the development of an adult learner’s reading habits as their lifetime literacy. In conducting this study, the researcher usednarrative inquiry as the method of the research. The data were collected through twice in-depth interviews with the participant. The data were analysed by using narrative three-dimensional aspects by Clandinin et.al (2013). In terms of temporality, the participant has experienced a reading habit since she was in Czech elementary school. Because her family maintains the habit, the reading habit remains until today. In terms of sociality, the role models of the reading habit are the participants' schoolmates and her father. In terms of spatiality, Czech has shaped the experience of the participants' reading habit. When she went back to Indonesia, the reading habit in Indonesian school was less exposed. This indicated that reading habits can be developed through the interaction of two key people. The first was the schoolteachers and the second was parents. The reading habits activity should be sustainable at school and at home.